Back Cover: Rational Design, Synthesis, and Biological Evaluation of Lactam‐Bridged Gramicidin A Analogues: Discovery of a Low‐Hemolytic Antibacterial Peptide (ChemMedChem 3/2015). Issue 3 (March 2015) - Mao, Ji; Kuranaga, Takefumi; Hamamoto, Hiroshi; Sekimizu, Kazuhisa; Inoue, Masayuki
<x xml:space="preserve">Abstract</x> The back cover picture shows a synthetic lactam‐bridged analogue of natural product gramicidin A (GA) inserting into the cell membrane where it functions as an ion channel and exerts its potent antibiotic activity. The helical GA backbone, the lactam bridge, and the ions are colored red, green and blue, respectively. The synthetic derivative maintained the potent antibiotic activity of GA but exhibited lower hemolytic and P388 cytotoxic activities. For further details, see the Full Paper by Masayuki Inoue et al. on p. 540 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>